Hyperpigmentation caused by vitamin B12 deficiency is completely reversible. - Jagadish Kumar, K.; Pavan Kumar, V.; Santhosh Kumar, M. (European Journal of Pediatric Dermatology, 2017)
Vitamin B12 deficiency may be due to congenital or acquired causes that involve reduced enteric gastrointestinal absorption of the vitamin. An exclusively vegetarian diet may be the source of vitamin B12 deficiency, as in the current case. Among the various problems secondary to vitamin B12 deficiency there is also a hyperpigmentation affecting both the skin and the oral mucosa, prevailing on the dorsal surface of the hands at the knuckles. The hyperpigmentation of the skin, whose pathogenesis is not yet clarified, is histologically due to incontinentia pigmenti. It is one of the most frequent signs of hypovitaminosis occurring in 80% of cases only in subjects with very dark phototype, not in Caucasians; it is often the sign of onset that leads the patient to the doctor. The hyperpigmentation regresses with the administration of vitamin B12.